Development and evaluation of educational intervention to promote informed decision making regarding embryo transfer in IVF patients - Rai, Vibha (2012)
Increasing the uptake of elective single embryo transfer is necessary to achieve the 10% HFEA limit for multiple IVF births in 2011. This thesis aims to explore patients’ and clinicians’ attitudes to eSET and to promote effective decision making regarding embryo transfer.